Comparative Transcriptome Analysis of Fungal Pathogen Bipolaris maydis to Understand Pathogenicity Behavior on Resistant and Susceptible Non-CMS Maize Genotypes - Meshram, Shweta; Gogoi, Robin; Bashyal, Bishnu Maya; Kumar, Aundy; Mandal, Pranab Kumar; Hossain, Firoz (Frontiers in Microbiology, 2022)
Bipolaris maydis is pathogen of maize which causes maydis leaf blight disease. In India major losses occur due to the B. maydis race “O” pathogen, whereas in other parts of the world, major losses are due to the race “T” pathogen. In the present study, we conducted an in planta transcriptomics study of the B. maydis race “O” pathogen after infection on non-CMS maize resistant and susceptible genotypes by mRNA sequencing to understand the molecular basis of pathogenicity for better management of the pathogen. Approximately 23.4 GB of mRNA-seq data of B. maydis were obtained from both resistant and susceptible maize backgrounds for fungus. Differentially expressed genes (DEGs) analysis of B. maydis in two different genetic backgrounds suggested that the majority of highly DEGs were associated with mitochondrial, cell wall and chitin synthesis, sugar metabolism, peroxidase activity, mitogen-activated protein kinase (MAPK) activity, and shikimate dehydrogenase. KEGG analysis showed that the biosynthetic pathways for secondary metabolism, antibiotics, and carbon metabolism of fungus were highly enriched, respectively, in susceptible backgrounds during infection. Previous studies in other host pathogen systems suggest that these genes play a vital role in causing disease in their host plants. Our study is probably the first transcriptome study of the B. maydis race “O” pathogen and provides in-depth insight of pathogenicity on the host.